#TITLE_ALTERNATIVE# - AQFALA MUGIARAYA (NIM: 15109054); Pembimbing: Dr.rer.nat. Poerbandono, RIFAKHRYZA
This research is intended to determine a tidal datum in Pulau Pramuka, Kepulauan Seribu, using a water level data. Tidal datum which is determined is HAT (Highest Astronomical Tide, MSL (Mean Sea Level), and LAT (Lowest Astronomical Tide). The methodology that aplied in determining HAT, MSL, and LAT is using a harmonic analysis for a ten months-water level data. The harmonic analysis produces 59 tidal components accompanied by Amplitude, Phase, SNR (Signal to Noise Ratio). Then, those tidal components are used to construct a tidal prediction for 18,6 years. In this reconstruction, only the components for which SNR is greater than 2 is included. The HAT and LAT value is determined by pick up the highest and the lowest value from the 18,6 years tidal prediction data. The MSL value is determined by computed the mean of the 18,6 years tidal prediction. The value of HAT, MSL, and LAT that obtained by harmonic analysis are -480,0 cm, -547,9 cm, and -601,6 cm, refers to the measurement reference, with +9,3 cm of standard deviation. The realibility level of these height references can be seen qualitatively, based on a number of tidal component involved in constructing tidal predictions, that is 45 tidal components.